2002
DOI: 10.1097/00024665-200211000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Web-based Information Resource at an Inner-city Community Church

Abstract: The objective of this project was to develop and implement electronic access to HIV/AIDS information resources at Glide Memorial Church in San Francisco, CA. This involved developing tailored Web-based access to the relevant information for the Glide Clinic patients. In addition, the project deployed workstations in 2 clinic areas and provided support to clinic patients as they learned to access the information resources. This article describes the experience with information retrieval in a clinic setting for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Some researchers have undertaken impressive work, demonstrating that Internet interventions can be used by and can benefit severely disadvantaged groups, including homeless drug users [25], single teenage mothers [26], and vulnerable elderly people [27]. In all of these studies, attention was paid both to providing access (eg, hardware and training in use of the system) and to accessibility (eg, ensuring the content and presentation were relevant and meaningful to the target audience).…”
Section: Pitfallsmentioning
confidence: 99%
“…Some researchers have undertaken impressive work, demonstrating that Internet interventions can be used by and can benefit severely disadvantaged groups, including homeless drug users [25], single teenage mothers [26], and vulnerable elderly people [27]. In all of these studies, attention was paid both to providing access (eg, hardware and training in use of the system) and to accessibility (eg, ensuring the content and presentation were relevant and meaningful to the target audience).…”
Section: Pitfallsmentioning
confidence: 99%
“…It has been shown that it is possible to deliver e- health interventions specifically designed for people with low literacy skills (e.g. Hispanics in Southern USA, [29], homeless drug users [30], and single teenage mothers [31]). What remains less clear is the extent to which people with low literacy skills will feel comfortable using a computer, or will be able to act on information or advice provided over the Internet.…”
Section: Introductionmentioning
confidence: 99%
“…They learned the importance of coaching by peers or health professionals to help patients navigate to useful sources, linking to sites with cultural relevance, and creating or promoting information with varied formats and literacy levels [1][2][3]6,8,9]. While some of the interventions contributed to modest changes in health indicators and stronger improvements in information awareness, they all required intensive support by peers or staff to encourage utilization.…”
Section: Introductionmentioning
confidence: 99%